Respuesta :
Answer:
[tex]f'(x)=2x[/tex]
Step-by-step explanation:
Given : Function [tex]f(x)=(x-3)(x+3)[/tex]
To find : The derivative of the function by using the Product Rule ?
Solution :
The product rule of derivative is
[tex]\frac{d}{dx}(u\cdot v)=uv'+vu'[/tex]
Here, u=x-3 and v=x+3
[tex]\frac{d}{dx}((x-3)\cdot (x+3))=(x-3)\frac{d}{dx}(x+3)+(x+3)\frac{d}{dx}(x-3)[/tex]
[tex]\frac{d}{dx}((x-3)\cdot (x+3))=(x-3)1+(x+3)1[/tex]
[tex]\frac{d}{dx}((x-3)\cdot (x+3))=x-3+x+3[/tex]
[tex]\frac{d}{dx}((x-3)\cdot (x+3))=2x[/tex]
Therefore, [tex]f'(x)=2x[/tex]
Answer:
[tex]f'(x)=2x[/tex]
Step-by-step explanation:
To Find :Find the derivative of the function by using the Product Rule. Simplify your answer. f(x) = (x - 3)(x + 3)
Solution :
[tex]f(x) = (x - 3)(x + 3)[/tex]
We will use chain rule of product
Formula : [tex]uv=u \times v' +v \tyimes u'[/tex]
=[tex](x-3) \times 1+(x+3) \times 1[/tex]
=[tex](x-3)+(x+3) [/tex]
=[tex]2x[/tex]
So, [tex]f'(x)=2x[/tex]
Hence the derivative of the function by using the Product Rule is 2x